ELECTRONIC SALES SYSTEM IN. TUMORA ANDALIS USING MICROSOFT VISUAL BASIC 6.0 - Onih Onih; Cut Asiana Gemawaty, SKom, MMSI Cut Asiana Gemawaty, SKom, MMSI (Jurnal Sistem Informasi, 2006)
System sales is a common activity for companies engaged in sale of goods or products produced by these companies. By applying the computerized system as efficiently as possible so that it makes the job especially in designing an application program used to compile the data processing.PT. TUMORA ANDALIS is a company engaged in electronics sales. In the operation of the system sales of PT. TUMORA ANDALIS running currently experiencing several problems. Funds therefore, the authors tried to design a computerized sales system using Microsoft Visual Basic 6.0, which is expected to support all sales activities of PT. TUMORA ANDALIS in order to be effective and efficient, so it is possible to minimize any errors caused by human error, mistakes maker reports sales, mistakes in data processing sales transactions that occurred at the PT. TUMORA ANDALIS.